Marketing Decision Making by Applying the Expert System (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
The main goal of this paper is to develop an expert system based on fuzzy set theory that will provide more successful and efficient decision making in the area of marketing, in relation with dilemma “to produce or to purchase”. Namely, authors will try to develop a model that will be suitable for making marketing decisions in production systems. Methodology in the paper obtained analysis of the theory of marketing, the development of the specific model for decision making, so as the application of developed model on one case from production system. Methodology which allows to model indeterminacy is fuzzy sets theory which is particularly well designed for dealing with non-probabilistic uncertainties. Authors will develop a model for decision making, based on successful integration of marketing and fuzzy theories. They will implement the model in decision making problem related to the debate “to produce or to purchase” on one real decision problem in production system. The main goal of this paper is to make changes in the work of decision makers in marketing sector. Authors pointed the advantages of the model with quality management, but also some limitations and possibilities for the future researches.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.